2013
DOI: 10.1123/jab.29.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Does Specific Footwear Facilitate Energy Storage and Return at the Metatarsophalangeal Joint in Running?

Abstract: Longitudinal midsole bending stiffness and elasticity are two critical features in the construction of running shoes. Stiff elastic materials (eg, carbon fiber) can be used to alter the midsole bending behavior. The purpose of this study was to investigate the effects of midsole stiffness and elasticity manipulation on metatarsophalangeal (MTP) joint mechanics during running in 19 male subjects at 3.5 m/s. Midsole bending stiffness and elasticity were modified by means of carbon fiber insoles of varying thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 36 publications
11
81
2
Order By: Relevance
“…During running, as the bending stiffness of the footwear is increased, the center of pressure under the foot will be shifted anteriorly [46,47]. This anterior shift of the ground reaction force will alter the moment arm to the ankle, knee, and hip joint of the athletes, with a more pronounced effect at the distal joints (i.e., ankle joint).…”
Section: Forefoot Stiffnessmentioning
confidence: 95%
See 1 more Smart Citation
“…During running, as the bending stiffness of the footwear is increased, the center of pressure under the foot will be shifted anteriorly [46,47]. This anterior shift of the ground reaction force will alter the moment arm to the ankle, knee, and hip joint of the athletes, with a more pronounced effect at the distal joints (i.e., ankle joint).…”
Section: Forefoot Stiffnessmentioning
confidence: 95%
“…Therefore, one possible mechanism of a performance benefit is that increasing forefoot stiffness results in a reduction of the energy loss at the MTP joint during joint extension [41,43,45,46] and/or by an increase in energy return at the MTP joint during joint flexion immediately before the instant of takeoff during stance [45,46]. Although this net change in energy has been shown to be relatively small (less than 1 J), if the net work done by the joint is minimally increased for each footfall during a run, this small energy savings may become substantial after many steps.…”
Section: Forefoot Stiffnessmentioning
confidence: 99%
“…It seems more likely that elastic materials in shoes increase the bending elasticity in the forefoot region which can influence GRF lever arms of lower extremity joints during the push-off phase (Willwacher, König, Braunstein, Goldmann, & Brüggemann, 2014); in other words, lowering energy consumption at a specific speed (Roy & Stefanyshyn, 2006). In addition, modifying the forefoot design of shoes facilitates the enhancement of athletic performance (Tinoco et al, 2010;Willwacher et al, 2013). However, designs with increased bending elasticity in the forefoot region of shoes cannot achieve a substantial amount of propulsive push-off impulse, possibly because higher bending elasticity in shoes increases the propulsive push-off force during walking and jogging while reducing the push-off time.…”
Section: Speedsmentioning
confidence: 98%
“…However, other studies have indicated that increasing the bending elasticity of shoe soles does not enhance jumping performance (Toon, Vinet, Pain, & Caine, 2011). Studies on forefoot designs have typically focused on increasing the insole stiffness (Tinoco et al, 2010;Willwacher, König, Potthast, & Brüggemann, 2013). This type of design might also increase the forefoot pressure and the contact between the foot portion and the elastic material might reduce deformation of the material and consequently constrain its ductility.…”
Section: Introductionmentioning
confidence: 95%
“…The last in the Type A shoes used in the study was designed on the basis of the sprint spike developed for a short-distance track in a previous study while using a hard material for the sole. Willwacher, König, Potthast and Brüggemann (2013) and Willwacher, König, Braunstein, Goldmann and Brüggemann (2014) have reported that the outsole and midsole with a high hardness in the forefoot region are effective not only in restricting movements of the metatarsophalangeal joint during running but also in returning energy to gain propulsion during running.…”
Section: Discussionmentioning
confidence: 99%